Communicating Gender and Advocating Accountability in Global Development - Wilkins, Karin Gwinn; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Case studies of micro-enterprise, girls' education, and population programs suggest that our discourse limits our potential to conceive of development, communication, and gender outside of neoliberal ideologies. Advocacy for global social justice demands a different accountability through critical research.
Keywords: Communication; Sociology; Economic development; Media Studies; Gender Studies; Development and Social Change